Food Safety and Nutrients of Terites, A Case Study in Kabanjahe, the city of Karo region, Sumatera Utara - Suparthana, IPutu; Perangin-angin, Ricky Suranta; Agung, IGusti Ngurah (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 2 No 2 (2015), 2015)
Terites is a traditional food of Karo’s people in Sumatera Utara which uniquely utilizematerials from cow’s rumen as a soup. This food is served, especially in the celebrating days,however now days terites is also served at the local restaurants in Kabanjahe, the capital city ofKaro region, Sumatera Utara. This study was aimed to investigate the food safety and nutrientcontents of terites which served in local restaurants in Kabanjahe. The investigations was usingpurposive sampling method, the samples were obtained from all of the restaurant which servedterites in Kabanjahe and analyze in the laboratory. The results showed that total microbe in thesamples was 2.4 x 104 cfu/g , negatively contaminated by E.coli and Salmonella spp. The dataare adequate to the national standard (SNI) for the food safety. The terites contains (average)19.9% protein, 15.4% fat and 1.68% crude fiber, which adequate as a good nutrient content.
Keywords: traditional food; terites; pagit-pagit; rumen